Sugarcane root distribution and growth as affected by genotype and crop cycle - Zhao,Liping (2020)
ABSTRACT Sugarcane (Saccharum L. spp. hybrids) is a globally important crop. While roots contribute to its net primary production, knowledge of sugarcane root growth is incomplete and limited in scope. The objective of this study was to determine cumulative root density (LA), root distribution, effective rooting depth (ERD), and root growth rate for four sugarcane genotypes across three crop cycles (plant cane [PC], first ratoon [FR], and second ratoon [SR]). The experiment was conducted in a rain shelter on four sugarcane genotypes (ROC22, YZ04-241, YZ05-194, and YZ05-51) using minirhizotron tubes to a soil profile depth of 1.08 m. Most roots in were found at 0–0.36 m-depth, and about 85.0% were within a 0–0.72 m depth in PC. In FR and SR, however, > 81.8% of roots were found at 0–0.54 m-depth regardless of genotype. The LA of ROC22 was often significantly higher than that of the other genotypes at depths < 0.54 m regardless of crop cycle. The genotype ROC22 had greater root length and faster root growth rate than YZ05-194 at 0.18–0.36 m in PC and FR, while SR YZ05-194 had slower root growth than the other genotypes at 0–0.18m. Ratooning ability of sugarcane genotypes may be related to these root growth attributes.